A comparative study of high-pressure processing and microwave pasteurisation on the formation of hydroxymethylfurfural in stingless bee (Heterotrigona itama) honey - Mohd Baroyi, Syahrul Anis Hazwani; Yusof, Yus Aniza; Chin, Nyuk Ling; Othman, Siti Hajar; Mohamad Ghazali, Nashratul Shera (AME Publishing Company, 2022)
Background: Hydroxymethylfurfural (HMF) concentration is recognised as a honey freshness indicator because this compound is typically absent in fresh honey or available in relatively small amounts. However, HMF has been alleged to have detrimental effects on human health and should be avoided for consumption if the content exceeds the permissible values of 30 mg/kg by Malaysian Standard MS 2683 [2017] and 40 mg/kg by the Codex Alimentarius Commission [2001]. Therefore, this study aimed to investigate the effect of modern alternative processing methods [high-pressure processing (HPP) and microwave pasteurisation (MW)] on the formation of HMF and other physicochemical properties of stingless bee (Heterotrigona itama) honey. Methods: Stingless bee honey was subjected to two different modern processing methods of HPP (5–30 min, 600 MPa) and MW (80 s, 700 W) and was stored in glass bottles at room temperature (25±1 ℃, 60% RH). The physicochemical properties of the honey were analysed for four consecutive weeks for a honey storage stability study. Results: In comparison to untreated honey, both treatments had no effect on the moisture level, pH, free acidity, and viscosity of the honey. Meanwhile, as the storage period progressed, the colour intensity increased. All sugar concentrations decreased significantly, which might be due to the Maillard reaction. At the end of the storage study, neither processing method prevented the formation of HMF in the honey, which can be harmful to consumers. Conducting HPP for 30 min increased the HMF level from 0 to 7.13 mg/kg in 4 weeks of storage. Meanwhile, MW-treated honey contained HMF after treatment (0.59 mg/kg) and increased to 10.98 mg/kg in the same period of storage study. Conclusions: It has been determined that modern processing methods are not feasible for processing such honey as it will result in the development of HMF, which is known to pose a health concern to honey consumers.